Direct generation of genuine single-longitudinal-mode narrowband photon pairs. (July 2015) - Luo, Kai-Hong; Herrmann, Harald; Krapick, Stephan; Brecht, Benjamin; Ricken, Raimund; Quiring, Viktor; Suche, Hubertus; Sohler, Wolfgang; Silberhorn, Christine
Abstract The practical prospect of quantum communication and information processing relies on sophisticated single-photon pairs, which feature a controllable waveform, narrow spectrum, excellent purity, fiber compatibility, and miniaturized design. For practical realizations, stable, miniaturized, low-cost devices are required. Sources with one or some of the above characteristics have already been demonstrated, but it is quite challenging to obtain a source with all of the described characteristics simultaneously. Here we report on an integrated single-longitudinal-mode, non-degenerate, narrowband photon pair source that exhibits all the requirements needed for quantum applications. The device is composed of a periodically poled, Ti-indiffused, lithium niobate waveguide with high reflective dielectric mirror coatings deposited on the waveguide end-faces. Photon pairs with wavelengths around 890 and 1320 nm are generated via type II phase-matched parametric down-conversion (PDC). Clustering in this dispersive cavity restricts the whole conversion spectrum to one single-longitudinal mode in a single cluster, yielding a narrow bandwidth of only 60 MHz. The high conversion efficiency in the waveguide, together with the spectral clustering in the doubly resonant waveguide, leads to a high brightness of <?CDATA 3× 10^4?> <?MML 3 × <!–RemoveAttribute_Superscriptshift–> 10 <!–mstyle_mmlmsup_level_1_open–> 4 <!–mstyle_mmlmsup_level_1_close–> ?><inline-graphic xlink:href="ark:/27927/pgj2j50jsjw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> pairs/(s mW MHz). This source exhibits prominent single-longitudinal-mode purity and remarkable temporal shaping capability. In particular, due to temporal broadening, we can observe that the coherence time of the two-photon component of the PDC state is actually longer than that of the single-photon states. The miniaturized monolithic design enables this source to have various fiber communication applications.